Clinical trials in gynecological cancer. Issue 3 (1st May 2007) - Trimble, E. L.; Davis, J.; Disaia, P.; Fujiwara, K.; Gaffney, D.; Kristensen, G.; Ledermann, J.; Pfisterer, J.; Quinn, M.; Reed, N.; Schoenfeldt, M.; Thigpen, J. T.; et al.
Abstract : The Gynecologic Cancer Intergroup is comprised representatives from international gynecological cancer trials organizations, which collaborate in multicenter studies to answer the clinical challenges in gynecological cancer. This review article highlights the key clinical questions facing clinical trialists over the next decade, the information and infrastructure resources available for trials, and the methods of trial development. We cover human papillomavirus (HPV)-associated neoplasia, including cervical cancer, together with endometrial cancer, ovarian cancer, and vulvar cancer. Infrastructure for clinical trials includes a database for trials, templates for protocol development, patient educational material, and financial support for clinical trials. Other critical issues include support from government and charities and government regulations.